The Influence of Online Customer Reviews, Online Customer Ratings, Influencers on Purchasing Decisions for Skincare Products on the Sociolla Application - Dwi Puspitaningrum, Hapsari; Arumsari, Nurul Rizka; Karatri, Rhealin Hening (Universitas Indo Global Mandiri Palembang, 2024)
The aim of this research is to analyze the influence of online customer reviews, online customer ratings and influencers on the decision to purchase skincare products on the Sociolla application. The approach used in this research is a quantitative approach. Consumers who have purchased skincare products using the Sociolla application with certain criteria are the sample in this study, totaling 100 respondents and sampling using a purposive sampling technique. The data collection technique uses a questionnaire method. The data analysis technique uses SPSS version 26. The research results show that the online customer review variable has a positive effect on purchasing decisions for skincare products on the Sociolla application. Online customer ratings have a positive influence on purchasing decisions for skincare products on the Sociolla application. Meanwhile, the influencer variable does not have a significant effect on purchasing decisions for skincare products on the Sociolla application